A high-frequency polymorphism in exon 6 of the CD45 tyrosine phosphatase gene (PTPRC) resulting in altered isoform expression. - Stanton, T; Boxall, S; Hirai, K; Dawes, R; Tonks, S; Yasui, T; Kanaoka, Y; Yuldasheva, N; Ishiko, O; Bodmer, W; Beverley, P; Tchilian, E (2003)
CD45 (leukocyte common) antigen is a hemopoietic cell-specific tyrosine phosphatase essential for antigen receptor-mediated signaling in lymphocytes. The molecule undergoes complex alternative splicing in the extracellular domain, and different patterns of CD45 splicing are associated with distinct functions. Lack of CD45 leads to severe combined immunodeficiency, and alterations of CD45 splicing, because of a polymorphism in exon 4, have been associated with altered immune function. Here we describe a polymorphism in exon 6 (A138G) of the gene encoding CD45 that interferes with alternative splicing. The polymorphism results in an amino acid substitution of Thr-47 to Ala in exon 6, a potential O- and N-linked glycosylation site. This exon 6 A138G variant is present at a frequency of 23.7% in the Japanese population but is absent in Caucasoids. Peripheral blood T cells from individuals carrying the A138G variant show a significant decrease in the proportion of cells expressing the A, B, and C CD45 isoforms and a high frequency of CD45R0+ cells. These phenotypic alterations in the A138G carriers may lead to changes in ligand binding, homodimerization of CD45, and altered immune responses, suggesting the involvement of natural selection in controlling the A138G carrier frequency.